UJI ANTIPIRETIK INFUSA DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP MENCIT JANTAN (Mus muculus) YANG DIDEMAMKAN - Engki Restulangi; Christianto Adhy Nugroho; Leo Eladisa Ganjari (Program Studi Biologi - Universitas Katolik Widya Mandala Surabaya (kampus Kota Madiun), 2020)
One of the health problems that often and usually appears is fever. Fever is heat regulation at a higher temperature level and is a common symptom that usually accompanies almost all infections. The study was conducted to determine the antipyretic effect of noni (Morindra citrifolia L.) leaf infusion against male mice (Mus muculus) by the artificial fever injection method using DPT vaccine. The test animals were male mice which were divided into 5 groups, each consisting of 4 mice. Group I as a positive control was given 0.5 ml of distilled water, group II as a negative control was given 65 mg / Kg BW of paracetamol, groups III, IV and V as a test group were given 2.5 ml / 100 g BW of noni leaf infusion with their respective concentrations 10%, 20% and 30% respectively. Observations were made on changes in temperature (ºC) of the test animals after being given the treatment. The data obtained were then tabulated in tables and graphs. The results showed that there was a decrease in temperature in the group of mice given noni leaf infusion. Thus it can be concluded that the noni leaf infusion has an antipyretic effect on male mice (Mus muculus).